Expectations Management - Versano, Tsahi; Trueman, Brett (The Accounting Review, 2017)
ABSTRACT This paper analyzes a manager's optimal expectations management strategy in a setting in which the manager provides forecast guidance to an analyst both privately and publicly. Conventional wisdom suggests that managers use private communications with analysts and public earnings forecasts interchangeably to guide analysts' earnings forecasts downward toward lower earnings targets. Our analysis shows that in markets with rational investors, private and public guidance play very different roles in managing expectations, and that managers benefit from downward guidance only in their private communication with analysts. In their public forecasts, they benefit from introducing an upward bias. We explore how the effectiveness of the private and public channels in communicating information to analysts affects managers' incentive to engage in expectations management, and provide a number of empirical predictions. Among other results, we show how reducing private communication between managers and analysts (through means such as Regulation Fair Disclosure) can increase price efficiency, weaken managers' motivation to engage in private, as well as public, expectations management, and increase managers' motivation to provide public disclosures.